(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Background: The loss of smell and taste in COVID-19 patients is now acknowledged as one of the disease’s primary symptoms. Objective: The aim of this study was to investigate the incidence of loss of smell and taste in outpatients and hospitalized patients with SARS-CoV-2 infection that RT-PCR had confirmed. Methodology: This cross-sectional study was conducted in the in the Novus Molecular Lab, Dhaka between 5 June 2021 and 17 July 2021]. COVID-19 patients were included in this study who become RT-PCR positive in nasopharyngeal and oropharyngeal swabs in a single center. All of them were interviewed by a structured questionnaire over the phone. Results: Among 200 COVID-19-positive patients smell and taste dysfunction appeared among 75(37.5%) patients. Only smell dysfunction occurred in 57.0% of patients, and taste dysfunction appears in 34.0% patients, and both symptoms were present among 9.0% of patients with or without other symptoms of COVID-19. The smell and taste recovery time was distributed as 63.0% recovered within less than a week, 20.0% within 2 weeks, and 17.0% in 2 weeks. Conclusion: In conclusion significant number of COVID-19 patients are presented with loss of smell and taste. Bangladesh Journal of Infectious Diseases June 2021;8(1):32-35